An archetype of the electron-unobstructed core–shell composite with inherent selectivity: conductive metal–organic frameworks encapsulated with metal nanoparticles. Issue 27 (6th July 2022) - Si, Xiaomeng; Zhao, Haojie; Yi, Beili; Zhou, Li; Ling, Yang; An, Yuanyuan; Wang, Yanli; Lee, Hiang Kwee; Tsung, Chia-Kuang; Ma, Yanhang; Chou, Lien-Yang
Abstract : This work represents the novel example of core-shell NPs@conductive MOFs applied in electrocatalysis. This composite exhibits the ability to expedite electron transfer with different thicknesses of electrode materials through direct interfaces. Abstract : The acquisition of monodisperse metal nanoparticles covered by conductive metal–organic frameworks (cMOFs) is an archetype of an electron-unobstructed core–shell composite, valued for its potential electrocatalytic ability and selectivity enhancement. In this work, Pt@cMOF composites with direct interfaces showed better performance in the oxygen reduction reaction than composites with indirect interfaces or with lower electroconductivity shells. This composite was proved to exhibit the ability to expedite electron transfer with different thicknesses of electrode materials. The detailed mechanism was studied by exploring the conductivity of shell materials, interfaces between cores and shells, and the surface electronic structure of the nanoparticles. We also report reaction selectivity from the inherent porous shells in the selective reduction of cinnamyl alcohol.